Protein-Ligand Fishing in planta for Biologically Active Natural Products Using Glutathione Transferases - Dixon, David P.; Edwards, Robert (Frontiers in Plant Science, 2018)
Screening for natural products which bind to proteins in planta has been used to identify ligands of the plant-specific glutathione transferase (GST) tau (U) and phi (F) classes, that are present in large gene families in crops and weeds, but have largely undefined functions. When expressed as recombinant proteins in E. coli these proteins have been found to tightly bind a diverse range of natural product ligands, with fatty acid- and porphyrinogen-derivatives associated with GSTUs and a range of heterocyclic compounds with GSTFs. With an interest in detecting the natural binding partners of these proteins in planta, we have expressed the two best characterized GSTs from Arabidopsis thaliana (At), AtGSTF2 and AtGSTU19, as Strep-tagged fusion proteins in planta. Following transient and stable expression in Nicotiana and Arabidopsis respectively, the GSTs were recovered using Strep-Tactin affinity chromatography and the bound ligands desorbed and characterised by LC-MS. AtGSTF2 predominantly bound phenolic derivatives including S-glutathionylated lignanamides and methylated variants of the flavonols kaempferol and quercetin. AtGSTU19 captured glutathionylated conjugates of oxylipins, indoles and lignanamides. Whereas the flavonols and oxylipins appeared to be authentic in vivo ligands, the glutathione conjugates of the lignanamides and indoles were artefacts formed during extraction. When tested for their binding characteristics, the previously undescribed indole conjugates were found to be particularly potent inhibitors of AtGSTU19. Such ligand fishing has the potential to both give new insight into protein function in planta as well as identifying novel classes of natural product inhibitors of enzymes of biotechnological interest such as GSTs.